Fred Unboxed, The Fred Rogers Center at Saint Vincent College, Latrobe, Pennsylvania - Long, Christopher (Archivaria, 2021)
Fred Unboxed. The Fred Rogers Center at Saint Vincent College, Latrobe, Pennsylvania. February 2020 – ongoing. Curated by Emily A. Uhrin.